Studi tentang Polaritas dan Sifat Elektrolit Buah Impor melalui Percobaan Sederhana - Siti Rahmah Maibang; Fadiya Malona Nasution; Marisa Manullang; Syifa Namira Damanik; Anggita Rahma Siregar; Yulika Hotrina Turnip; Iis Siti Jahro (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This study was conducted to examine the polarity and electrolyte properties of several types of imported fruit that are increasingly consumed by the Indonesian people after the Covid-19 pandemic. The method used was a laboratory experiment conducted using three types of polar-nonpolar solvents and a simple multimeter-based electrolyte circuit to measure conductivity by testing extracts of ten imported fruits (melon, dragon fruit, strawberry, kiwi, pomegranate, grapes, cherries, lemon peel, blueberries, and dates). The polarity test was carried out using three different solvents (water, vinegar, and cooking oil), while the electrolyte properties were observed with a simple electrical circuit. The results showed that most of the extracts were soluble in water and vinegar, but not in cooking oil, so the majority of the fruit components were polar. Lemon peel and melon peel have semi-polar properties due to their essential oil content. In the electrolyte test, fruits with high acid content (lemon, pomegranate, strawberry) act as strong electrolytes, while fruits with high sugar content (dates, melon) are only classified as weak electrolytes. Other fruits such as grapes, kiwi, and blueberries show moderate electrolyte properties. These findings support basic chemical concepts regarding the relationship between polarity, solubility, and electrical conductivity, and can be utilized in teaching and food technology applications.